1988
DOI: 10.1172/jci113445
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic sodium absorption in rabbit cecum in vitro.

Abstract: Regional variations in the ion transport properties of the colon may have significant physiological and pathophysiological implications. However Thus, cecum exhibits a distinct type of electrogenic Na electrogenic Na absorption which is partially dependent on the presence of Cl and HCO3, not blocked by amiloride but by phenamil. Because of its large surface area and its novel mechanism of electrogenic Na transport, the cecum exerts an important regulatory role in colonic fluid and electrolyte balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Halevy et al (25) reported that RU 28362 infused into rats for 24 h increased amiloride-insensitive Isc which may represent either active chloride secretion or amiloride-resistant, electrogenic sodium transport. The former has been shown to be stimulated by dexamethasone and methylprednisolone in rat distal colon (26) and rat ileum (27), respectively, and the latter was recently described in the rabbit cecum (28). Unfortunately, neither ion flux measurements nor ion replacement studies were performed to establish the basis for this increase in Isc.…”
Section: Discussionmentioning
confidence: 99%
“…Halevy et al (25) reported that RU 28362 infused into rats for 24 h increased amiloride-insensitive Isc which may represent either active chloride secretion or amiloride-resistant, electrogenic sodium transport. The former has been shown to be stimulated by dexamethasone and methylprednisolone in rat distal colon (26) and rat ileum (27), respectively, and the latter was recently described in the rabbit cecum (28). Unfortunately, neither ion flux measurements nor ion replacement studies were performed to establish the basis for this increase in Isc.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the guinea-pig distal colon, in the caecum the electrogenic part of Na+ absorption appears to be relatively insensitive to amiloride inhibition (Rechkemmer, 1988). Amiloride-insensitive electrogenic Na+ transport has recently been demonstrated for the rabbit caecum (Sellin, Oyarzabal & Cragoe, 1988). In contrast to the rabbit caecum, however, in the guinea-pig caecum incubation with a Na+-free solution led to a drastic increase in tissue conductance.…”
Section: Na+-h+ Exchange and Scfa Transportmentioning
confidence: 98%
“…In addition, surgical masks and disposable gloves were used. In the proximal colon of rats, sodium is transported across the apical membrane by an electroneutral Na + /H + exchange (Binder et al, 1986;Foster et al, 1986a, b (Sellin et al, 1988). !!…”
Section: Animals and Preparationsmentioning
confidence: 99%